Pain Perception following Initial Closed Reduction in the Preoperative Care of Unstable, Dorsally Displaced Distal Radius Fractures - Löw, Steffen; Papay, Marion; Eingartner, Christoph (Journal of Hand and Microsurgery, 2019)
Introduction Closed reduction and cast immobilization is a common practice as initial treatment for distal radius fractures. This study examines the pain perception that accompanies this approach.Materials and Methods Thirty dorsally displaced distal radius fractures were reduced and casted under finger-trap traction with intravenous analgesics. Patients rated their pain perception on visual analog scale prior to presentation, during reduction, during casting, and for every day until surgery. Closed reduction improved palmar tilt from −26.3 to −10.8 degrees. Surgery improved palmar tilt from −10.8 to +6.1 degrees. Closed reduction improved radial inclination from 15.5 to 19.1 degrees. Surgery improved radial inclination from 19.1 to 21.6 degrees. Mean pain perception was 5.8 at presentation. Reduction increased pain to 7.5 (p < 0.001), whereas casting was less painful (3.7; p < 0.001). At the evening following casting and the following days until surgery, mean pain was still as high as 4.1, 4.2, 4.1, 3.6, 3.9, 2.8, 3.0, and 3.0, with some patients experiencing more pain than initially.Conclusion Reduction generates significant pain with only minor relief during cast immobilization. The indication for closed reduction prior to cast application is therefore questionable.
Keywords: cast immobilization; closed reduction; Colles’ fractures; complex regional pain syndrome; distal radius fracture; pain perception